A copper-barium-tin-sulfur-selenium five-element semiconductor alloy and its preparation method and application

The preparation of copper barium tin sulfide and selenization five-member semiconductor alloys was solved by vacuum smelting and selenization, and the problem of disorderly position of zinc ions and tin ions in existing copper zinc tin selenium materials affecting the photoelectric conversion efficiency, and the light absorption performance of the alloy is improved It has a uniform phase structure and is suitable for high-efficiency solar cells.

CN115347064BActive Publication Date: 2025-02-21SHENYANG LIGONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210085358.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-25
Publication Date
2025-02-21
Estimated Expiration
2042-01-25

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of existing copper-zinc-tin-selenium-selenium-film solar cells has not been broken through, mainly because the disorder of the position of zinc ions and tin ions in the crystal lattice affects the photoelectric performance of the material.

Method used

The copper barium tin-sulfur semiconductor alloy was prepared by vacuum smelting, and the selenium element was partially replaced by selenization treatment to form a copper barium tin sulfur-selenium five-membered semiconductor alloy.

Benefits of technology

The light absorption performance of the alloy is improved through selenization treatment, forming a uniform-phase structure of copper barium tin sulfide selenium material, which is suitable for P-type light absorption layer of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115347064B_ABST
    Figure CN115347064B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of alloys, and discloses a copper-barium-tin-sulfur-selenium five-element semiconductor alloy and a preparation method thereof, wherein the atomic ratio of the elements in the alloy is: copper 1.5-2, barium 0.7-1, tin 0.7-1, sulfur 1.8-2.5, selenium 2-2.5; the preparation method of the alloy comprises: according to the above atomic ratio, each weighed preparation raw material is smelted in a vacuum and protective atmosphere in stages to obtain a copper-barium-tin-sulfur semiconductor alloy; then the copper-barium-tin-sulfur semiconductor alloy and the weighed selenium particles are placed in a graphite box together, and selenization treatment is continued in a protective gas atmosphere to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy. The novel copper-barium-tin-sulfur five-element semiconductor alloy prepared by the invention is a P-type semiconductor, and the material can be applied to solar cells and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloys, and in particular to a copper-barium-tin-sulfur-selenium quinary semiconductor alloy and a preparation method and application thereof. Background Art

[0002] The main direction of new energy development is how to better and more efficiently utilize clean energy such as wind energy, tidal energy, and solar energy. Solar energy has become a hot topic of research in the current scientific and industrial communities because it is not restricted by geography and environment. Solar energy can be converted into heat energy and electrical energy. In recent years, with the rapid development of power technology, solar power generation and grid connection have entered the daily life of the general public. At present, the scientific and industrial communities are focusing more and more on finding solar cell light-absorbing layer materials with high-efficiency photoelectric conversion materials. Solar cell light-absorbing layer materials are the core of solar cells. The appropriate band gap width, high carrier concentration, long-term high-efficiency stability of the light-absorbing layer materials, as well as the environmental protection of the material itself and the manufacturing cost that the business community can afford are several key factors to consider when selecting solar cell light-absorbing layers.

[0003] Currently, commercial thin-film solar cells use silicon-based materials as the light-absorbing layer. Although silicon has price and cost advantages in the commercialization process, the pollution in the production process of silicon thin-film solar cells and the efficiency degradation of silicon thin-film solar cells have led the scientific and industrial communities to continue to strive to find new thin-film solar cell materials.

[0004] Inorganic thin-film solar cells have become a research hotspot in the field of solar cells due to their low light-absorbing layer material and high photoelectric conversion efficiency. Quaternary semiconductor alloys represented by copper indium gallium selenide have been widely studied. The laboratory photoelectric conversion efficiency of such thin-film solar cells exceeds 23% in a short time, and the photoelectric conversion efficiency of industrial components exceeds 15%, reaching a level comparable to that of silicon thin-film solar cells; however, the light-absorbing layer of copper indium gallium selenide thin-film cells contains metal indium and gallium, which are not abundant elements and are scarce resources. At the same time, transparent conductive glass ITO, i.e. indium tin oxide, requires a large amount of indium, which greatly reduces the stock of indium. Therefore, researchers and engineers are looking for new alternative materials. The quaternary semiconductor material copper zinc tin selenide is used in thin-film solar cells because of its similar structure and photoelectric properties to copper indium gallium selenide. Dr. DB Mitzi of IBM used the hydrazine solution method to prepare the light-absorbing layer of copper zinc tin selenium thin-film solar cells, assembled solar cell devices, and obtained a photoelectric conversion efficiency of 12.6% in 2012. However, there has been no breakthrough in this efficiency since 2012. The reason is that the disordered position of zinc ions and tin ions in the lattice of the copper-zinc-tin-selenium light-absorbing layer affects the further improvement of the photoelectric conversion efficiency of copper-zinc-tin-selenium thin-film solar cells.

[0005] In order to solve the above-mentioned deficiencies in the prior art, the present invention provides a copper-barium-tin-sulfur-selenium quinary semiconductor alloy material and a preparation method and application thereof. Summary of the invention

[0006] In order to solve the deficiencies in the above-mentioned prior art, the present invention provides a copper-barium-tin-sulfur-selenium five-element semiconductor alloy material and its preparation method and application. The present invention adopts the means of vacuum melting to prepare a copper-barium-tin-sulfur-selenium five-element semiconductor alloy material, using cuprous sulfide, barium sulfide, and tin disulfide as raw materials, using the means of vacuum melting, and adopting the solid-liquid-solid reaction principle to prepare a copper-barium-tin-sulfur four-element semiconductor alloy. This method avoids the sublimation and volatilization of the sulfur element in the component during the preparation of the alloy, resulting in the loss of the sulfur element, and at the same time avoids the use of metal element mixed with sulfur, the enthalpy change during the reaction is large, and the risk of explosion caused by the heat release of the reaction is avoided. Subsequently, the selenization method is adopted to partially replace the sulfur element in the copper-barium-tin-sulfur alloy with the selenium element. The selenium element replaces the sulfur element to obtain a copper-barium-tin-sulfur-selenium alloy with better light absorption. The physical phase analysis is performed on it to obtain a copper-barium-tin-sulfur-selenium material with uniform physical phase.

[0007] The copper-barium-tin-sulfur-selenium five-element semiconductor alloy material and the preparation method thereof of the present invention are realized by the following technical scheme:

[0008] The first object of the present invention is to provide a copper-barium-tin-sulfur-selenium quinary semiconductor alloy, the atomic ratio of which is:

[0009] Copper 1.5-2, barium 0.7-1, tin 0.7-1, sulfur 1.8-2.5, selenium 2-2.5.

[0010] Furthermore, the atomic ratio of the element composition of the copper-barium-tin-sulfur-selenium quinary semiconductor alloy is:

[0011] Copper 1.8-2, barium 0.8-1, tin 0.8-1, sulfur 1.8-2.2, selenium 2-2.2.

[0012] The second object of the present invention is to provide a method for preparing the copper-barium-tin-sulfur-selenium quinary semiconductor alloy, comprising the following steps:

[0013] Step 1, according to the above atomic ratio, weigh the corresponding masses of cuprous sulfide, barium sulfide, tin disulfide and selenium particles respectively;

[0014] Step 2, placing the weighed cuprous sulfide, barium sulfide and tin disulfide under vacuum conditions and in a protective gas atmosphere, and performing segmented smelting to obtain a copper-barium-tin-sulfur semiconductor alloy;

[0015] Step 3, placing the copper-barium-tin-sulfur semiconductor alloy and the weighed selenium particles in a tubular furnace, first performing a vacuum treatment, then filling with nitrogen at a nitrogen flow rate of 30 ml per minute, and performing a selenization treatment at a temperature of 450-580° C. for 2 hours, cooling with the furnace, to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy.

[0016] Furthermore, the molar ratio of cuprous sulfide, barium sulfide and tin disulfide is 0.75-1:0.7-1:0.7-1.

[0017] Furthermore, in step 3, the copper-barium-tin-sulfur semiconductor alloy and the weighed selenium particles are placed in a graphite box for selenization treatment.

[0018] Furthermore, the protective gas is nitrogen, and the flow rate of the nitrogen is 25-30 mL / min.

[0019] Furthermore, in step 2, the vacuum degree of the vacuum condition is 0.3×10 5 ~0.5×10 5 Pa.

[0020] Furthermore, in step 2, the staged smelting is first heated to 650-800°C, and after all three raw materials are melted, the temperature is then raised to 850-1250°C for smelting for 30-60 minutes, and then slowly cooled in the furnace to obtain a copper-barium-tin-sulfur semiconductor alloy.

[0021] The third object of the present invention is to provide an application of the copper-barium-tin-sulfur-selenium quinary semiconductor alloy in the preparation of solar cells.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention uses cuprous sulfide, barium sulfide and tin disulfide as metal precursors, and uses a vacuum induction furnace to heat a quartz test tube. After reaching the melting point of the three substances, cuprous sulfide, barium sulfide and tin disulfide undergo a solid phase fusion reaction, thereby preparing a copper-barium-tin-sulfur semiconductor alloy, avoiding the sublimation and volatilization of sulfur elements in the components during the alloy preparation process, resulting in the loss of sulfur elements, and avoiding the use of metal single elements mixed with sulfur, which increases the enthalpy change during the reaction process, and avoids the risk of explosion caused by the heat release of the reaction. Subsequently, the prepared copper-barium-tin-sulfur semiconductor alloy and selenium particles are placed in graphite, placed in a vacuum induction furnace, and the furnace is evacuated, selenized at 450°C-580°C for 2 hours, and then filled with nitrogen. The selenium vapor generated during the selenization process can react with the copper-barium-tin-sulfur semiconductor, so that a part of the selenium atoms can spontaneously replace the sulfur atoms in the copper-barium-tin-sulfur semiconductor alloy to generate a light-absorbing copper-barium-tin-sulfur-selenium five-element semiconductor alloy, thereby improving the light absorption performance of the alloy. In addition, the novel copper-barium-tin-sulfur five-element semiconductor alloy prepared by the present invention is a P-type semiconductor, and the material can be applied to the fields of solar cells and the like.

[0024] The present invention firstly prepares a copper-barium-tin-sulfur semiconductor alloy by a vacuum induction heating method, and then adopts a solid-gas reaction method, i.e., a reaction of selenium vapor with the copper-barium-tin-sulfur alloy, to prepare a novel copper-barium-tin-sulfur-selenium quinary semiconductor alloy, which is a P-type semiconductor. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD spectrum of the copper-barium-tin-sulfur-selenium alloy in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0027] Example 1

[0028] The present invention provides a copper-barium-tin-sulfur-selenium quinary semiconductor alloy, and the preparation method thereof is as follows:

[0029] 1 mol of cuprous sulfide, 1 mol of barium sulfide and 1 mol of tin disulfide were placed in a quartz glass test tube, which was evacuated, sealed and placed in a vacuum induction furnace. The vacuum induction furnace was evacuated, and then nitrogen or argon gas was introduced as a protective gas to make the vacuum degree in the vacuum induction furnace 0.3×10 5 -0.5×10 5 Pa, then heat up to 680℃, after the three raw materials are melted, heat up to 1000℃, smelt for 35min, and slowly cool along with the furnace to obtain copper-barium-tin-sulfur semiconductor alloy.

[0030] The copper-barium-tin-sulfur semiconductor alloy prepared above and 2 mol of selenium particles were loaded into graphite and placed in a vacuum induction furnace. The furnace was evacuated and then filled with nitrogen at a rate of 30 mL / min. The furnace was selenized at 530°C for 1 hour and cooled to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy.

[0031] The analysis results of the atomic ratio of copper, barium, tin, sulfur and selenium are: copper (Cu): 1.98, barium (Ba): 0.98, tin (Sn): 0.96, sulfur (S): 1.96, and selenium (Se): 1.98.

[0032] Example 2

[0033] The present invention provides a copper-barium-tin-sulfur-selenium quinary semiconductor alloy, and the preparation method thereof is as follows:

[0034] 1 mol of cuprous sulfide, 0.8 mol of barium sulfide and 0.9 mol of tin disulfide were placed in a quartz glass test tube, which was evacuated, sealed and placed in a vacuum induction furnace. The vacuum induction furnace was evacuated, and then nitrogen or argon gas was introduced as a protective gas to make the vacuum degree in the vacuum induction furnace 0.3×10 5 -0.5×10 5 Pa, then heat up to 650 ° C, after the three raw materials are melted, heat up to 1100 ° C, smelt for 45 minutes, and slowly cool with the furnace to obtain copper-barium-tin-sulfur semiconductor alloy.

[0035] The copper-barium-tin-sulfur semiconductor alloy prepared above and 2.2 mol of selenium particles were placed in graphite and placed in a vacuum induction furnace. The furnace was evacuated and then filled with nitrogen at a rate of 30 mL / min. The alloy was selenized at 520°C for 1 hour and cooled in the furnace to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy.

[0036] The analysis results of the atomic ratio of copper, barium, tin, sulfur and selenium are: copper (Cu): 1.95, barium (Ba): 0.78, tin (Sn): 0.87, sulfur (S): 1.92, and selenium (Se): 2.03.

[0037] Example 3

[0038] The present invention provides a copper-barium-tin-sulfur-selenium quinary semiconductor alloy, and the preparation method thereof is as follows:

[0039] 0.9 mol of cuprous sulfide, 0.85 mol of barium sulfide and 0.9 mol of tin disulfide were placed in a quartz glass test tube, which was evacuated, sealed and placed in a vacuum induction furnace. The vacuum induction furnace was evacuated, and then nitrogen or argon gas was introduced as a protective gas to make the vacuum degree in the vacuum induction furnace 0.3×10 5 -0.5×10 5Pa, then heat up to 700℃, after the three raw materials are melted, heat up to 1050℃, smelt for 40min, and slowly cool along with the furnace to obtain copper-barium-tin-sulfur semiconductor alloy.

[0040] The copper-barium-tin-sulfur semiconductor alloy prepared above and 2.1 mol of selenium particles were placed in graphite and placed in a vacuum induction furnace. The furnace was evacuated and then filled with nitrogen at a rate of 30 mL / min. The alloy was selenized at 530°C for 1.5 hours and cooled in the furnace to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy.

[0041] The analysis results of the atomic ratio of copper, barium, tin, sulfur and selenium are: copper (Cu): 1.79, barium (Ba): 0.83, tin (Sn): 0.88, sulfur (S): 1.95, and selenium (Se): 2.07.

[0042] Example 4

[0043] The present invention provides a copper-barium-tin-sulfur-selenium quinary semiconductor alloy, and the preparation method thereof is as follows:

[0044] 0.85 mol of cuprous sulfide, 0.9 mol of barium sulfide and 0.85 mol of tin disulfide were placed in a quartz glass test tube, which was evacuated, sealed and placed in a vacuum induction furnace. The vacuum induction furnace was evacuated, and then nitrogen or argon gas was introduced as a protective gas to make the vacuum degree in the vacuum induction furnace 0.3×10 5 -0.5×10 5 Pa, then heat up to 750℃, after the three raw materials are melted, heat up to 1050℃, smelt for 45min, and slowly cool along with the furnace to obtain copper-barium-tin-sulfur semiconductor alloy.

[0045] The copper-barium-tin-sulfur semiconductor alloy prepared above and 2.2 mol of selenium particles were placed in graphite and placed in a vacuum induction furnace. The furnace was evacuated and then filled with nitrogen at a rate of 25 mL / min. The alloy was selenized at 530°C for 2 hours and cooled in the furnace to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy.

[0046] The analysis results of the atomic ratio of copper, barium, tin, sulfur and selenium are: copper (Cu): 1.68, barium (Ba): 0.85, tin (Sn): 0.82, sulfur (S): 1.92, and selenium (Se): 2.16.

[0047] Example 5

[0048] The present invention provides a copper-barium-tin-sulfur-selenium quinary semiconductor alloy, and the preparation method thereof is as follows:

[0049] 0.9 mol of cuprous sulfide, 0.9 mol of barium sulfide and 1 mol of tin disulfide were placed in a quartz glass test tube, which was evacuated, sealed and placed in a vacuum induction furnace. The vacuum induction furnace was evacuated, and then nitrogen or argon gas was introduced as a protective gas to make the vacuum degree in the vacuum induction furnace 0.3×10 5 -0.5×10 5 Pa, then heat up to 780℃, after the three raw materials are melted, heat up to 1150℃, smelt for 50min, slowly cool along with the furnace to obtain copper-barium-tin-sulfur semiconductor alloy.

[0050] The copper-barium-tin-sulfur semiconductor alloy prepared above and 2 mol of selenium particles were placed in graphite and placed in a vacuum induction furnace. The furnace was evacuated and then filled with nitrogen at a rate of 35 mL / min. The alloy was selenized at 530°C for 2 hours and cooled in the furnace to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy.

[0051] The analysis results of the atomic ratio of copper, barium, tin, sulfur and selenium are: copper (Cu): 1.78, barium (Ba): 0.88, tin (Sn): 0.98, sulfur (S): 2.28, and selenium (Se): 1.85.

[0052] Experimental part

[0053] In order to detect the performance of the alloy prepared by the method of the present invention, the present invention takes the alloy of Example 1 as an example and performs XRD test on it. The results are as follows: Figure 1 shown by Figure 1 It can be seen that the copper-barium-tin-sulfur-selenium alloy of Example 1 is a homogeneous phase structure.

[0054] The present invention also takes the alloy of Example 1 as an example, and performs Hall effect tests on the alloy of Example 1 at room temperature (298K) and a magnetic field strength of 5000 Gauss with different current intensities. The results are shown in Table 1.

[0055] Table 1 Hall effect test results of copper, barium, tin, sulfur and selenium

[0056]

[0057] Note: The positive value of the Hall coefficient indicates that the semiconductor is a P-type semiconductor.

[0058] On the contrary, the Hall coefficient is negative, and this type of semiconductor is an N-type semiconductor.

[0059] As can be seen from Table 1, the body Hall coefficient of the alloy in Example 1 is a positive value, indicating that the copper-barium-tin-sulfur-selenium alloy prepared in Example 1 is a P-type semiconductor. The P-type semiconductor alloy can be used as a P-type light-absorbing layer of a solar cell, and can be used in thin-film solar cells by reacting with an N-type semiconductor thin film such as cadmium sulfide, zinc sulfide, etc. to construct a PN junction.

[0060] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a copper-barium-tin-sulfur-selenium quinary semiconductor alloy, characterized in that: The atomic ratio of the copper, barium, tin, sulfur and selenium quinary semiconductor alloy is: Copper 1.8-2, barium 0.8-1, tin 0.8-1, sulfur 1.8-2.2, selenium 2-2.2; The preparation method of the copper-barium-tin-sulfur-selenium quinary semiconductor alloy comprises the following steps: Step 1, according to the above atomic ratio, weigh the corresponding masses of cuprous sulfide, barium sulfide, tin disulfide and selenium particles respectively; Step 2, placing the weighed cuprous sulfide, barium sulfide and tin disulfide under vacuum conditions and in a protective gas atmosphere, and performing segmented smelting to obtain a copper-barium-tin-sulfur semiconductor alloy; Step 3, placing the copper-barium-tin-sulfur semiconductor alloy and the weighed selenium particles in a graphite box, continuing to selenize at a temperature of 450-580° C. in a protective gas atmosphere, and cooling with the furnace to obtain a copper-barium-tin-sulfur-selenium five-element semiconductor alloy; In step 2, the staged smelting is to first heat the temperature to 650-800°C, and after all three raw materials are melted, heat the temperature to 850-1250°C and smelt for 30-60 minutes, and then slowly cool with the furnace to obtain a copper-barium-tin-sulfur semiconductor alloy.

2. The preparation method according to claim 1, characterized in that Selenization treatment for 2h.

3. The preparation method according to claim 1, characterized in that: The molar ratio of cuprous sulfide, barium sulfide and tin disulfide is 0.75-1:0.7-1:0.7-1.

4. The preparation method according to claim 1, characterized in that: The protective gas is nitrogen, and the flow rate of the nitrogen is 25-35 mL / min.

5. Use of a copper-barium-tin-sulfur-selenium quinary semiconductor alloy prepared by the preparation method according to claim 1 in preparing solar cells.

Citation Information

Patent Citations

  • Preparation method of Cu-Im-Ga-Se quaternary semiconductor alloy

    CN103572089A

  • Preparation method of copper barium (strontium / calcium) tin sulfur (selenium) thin film

    CN107195697A